The role of social sciences in the establishment of social behavior in the industrial revolution 4.0 - Paramita, Deliya; Safitri, Sani (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
This article aims to provide knowledge about the need to shape social behavior in the face of Industrial Revolution 4.0. One option is to study the social sciences. The interaction between parents, schools, teachers, and the social environment to enable the nation's prospective students to face and survive the Industrial Revolution 4.0 is also less critical. The method used to analyze this problem is a qualitative descriptive method, namely a literature study. This article's literature review involves extensive reference books, journal articles, conference proceedings, and many other scholarly manuscripts. Once collected, the research analysis is carried out according to the article's topic. The results of this study explain that: (1) When forming social behavior in social pedagogy, it can develop through personal, social, and intellectual abilities; (2) The social skills developed are respecting and appreciating each other; and (3) The ability to communicate and cooperate. Prosocial behavior; Ability to care for society in the environment; Strengthening the spirit of nationalism, understanding inequality and equality.